Integrative holistic approaches for children, adolescents, and young adults with sickle cell disease: A single center experience - Laila A. Mahmood; Lisa Thaniel; Brenda Martin; Stefanie Marguiles; Sarah Reece-Stremtan; Risi Idiokitas; Elizabeth Bettini; Steven J. Hardy; Ira Cohen; Megan Connolly; Deepika S. Darbari (Elsevier, 2021)
Context: Painful vaso-occlusive crises (VOCs) associated with sickle cell disease (SCD) are the most common cause of morbidity, hospitalizations, and poor quality of life. Additional symptoms such as sleep disturbances, fatigue, and stress are also common. Non-traditional approaches are often used by families, but concerns remain that patients may forgo standard of care effective therapies in favor of dangerous unproven alternatives. Objectives: To describe a single center experience related to a multidisciplinary integrative medicine clinic within the division of hematology dedicated to children and young adults with SCD. Methods: The Sickle Cell Integrative Clinic at Children's National Hospital services patients with SCD. The main goal of this clinic is to provide access to non-pharmacologic interventions, and to manage patients' symptoms in a holistic manner along with standard of care management of SCD. This IRB approved study evaluated experiences of both patients and parents who attended this clinic. Results: Thirty-seven unique patients attended this clinic over 2 years and 31 participated in the study. After attending the SCD integrative clinic, the majority of patients reported integrative therapies to be an acceptable way of treating pain and believed these to be effective. Overall, the vast majority (88 %) of patients reported having a positive experience with the therapies offered in the clinic. None of the patients experienced any adverse events related to integrative therapies provided in the clinic. Conclusion: Our experience suggests that encouraging conversations and offering safe and potentially effective integrative therapies alongside conventional SCD therapies under medical guidance allows patients to have an open discussion about their beliefs and treatment goals, improves patient satisfaction and can improve outcomes.